E-SPORT COMMUNITY MEDIA PLATFORMS - L. V. Sharahina; V. V. Boguslavskaja; A. O. Azizulova; E. A. Budnik (Дискурс, 2018)
The development of digital information technologies contributed to forming rather closed social communities in the media scene of the Internet communications. Such associations integrate representatives of different counties and various linguistic cultures sharing common interests. The article represents E-sport community as a structural element of Information society which members share the same communication infrastructure. Specific features and audience of e-sport media as an integration instrument of E-sport community are analyzed. E-sport and e-sport media opportunities for effective and tolerant inter-cultural collaboration are demonstrated.